ポーラー パトロール バルーン キョクイキ シュウカイ ダイキキュウ カンソク ニヨル オーロラ Xセン ノ コウイキ クウカン ブンプ オヨビ エネルギー スペクトル トクセイ - 鈴木, 裕武; スズキ, ヒロム; Suzuki, Hiromu (1996)
P(論文) 高エネルギー降下電子による制動放射X線の広域特性の観測を目的としたPolar Patrol Balloon (PPB) 6号機実験が南極域にて行われた。PPB-6号機は1993年1月5日昭和基地より放球され, 27日間で約一周半の極域周回飛行を達成し, オーロラX線の広域特性の観測に成功した。同一の観測装置によるオーロラX線の広域かつ長時間の観測は, 本実験により初めて成功した。解析の結果得られたオーロラX線の広域空間分布は昼間側でX線現象が卓越し, かつ, 小さなイベントながら不変磁気緯度55°以下の低緯度にまで広がっていた。また, ∿60°以下の低緯度で観測されたイベントの計数率時間変化は顕著な時間的構造を持たず, プラズマ圏ヒスの放射特性に似た特徴を示すものが多い事が分かった。オーロラX線のエネルギースペクトルは不変磁気緯度依存性を示し, ∿60°以上では緯度の低下とともにハードになり, ∿60°以下では高緯度よりソフトである。この不変磁気緯度に対する変化はサイクロトロン共鳴波動粒子相互作用に関する電子の共鳴エネルギーの不変磁気緯度に対する変化と一致しており, 電子の降下原因としてホイッスラーモードの電磁波とのサイクロトロン共鳴の可能性を示唆している。エネルギースペクトルは磁気地方時に関して依存性を示し, 時間の進行とともにハードになる傾向を示した。この磁気地方時依存性はドリフト電子のサイクロトロン共鳴に関連する軌道存続時間(ライフタイム)により説明が可能である。以上の観測結果はいずれも電子の降下原因としてサイクロトロン共鳴を示唆するものであり, 本論文はオーロラX線を放射する高エネルギー電子の降下原因がサイクロトロン共鳴により矛盾なく説明される可能性を, 初めて極域全体にわたるオーロラX線現象の観測結果から提示するものである。 Polar Patrol Balloon (PPB) No.6 experiment was performed over Antarctica, in order to observe wide-area characteristics of bremsstrahlung X-rays radiated from energetic precipitated electrons. PPB No.6 was launched from Syowa Station on 5 January 1993 and flew along one and a half circumpolar paths. Distinct enhancements of auroral X-rays were often observed during the entire flight period of 27 days. This is the first observation of broad-spatial distribution of auroral X-rays by a unique instrument onboard a long life balloon. X-ray enhancements were dominant in the magnetic local dayside, and some small enhancements were observed at low latitude below 60°. Such low latitude enhancements have simple temporal structures similar to plasmaspheric hiss. The harder spectrum events tend to occur in the lower invariant latitudes, except for a few events. Latitudinal dependence of auroral X-ray spectrum agrees with latitudinal dependence of characteristic energy for cyclotron resonance. Diurnal energy variation of the X-ray spectrum was observed. This variation can be explained by theoretical precipitation lifetime on cyclotron resonance. All of the observed facts suggest that energetic electron precipitation is caused by cyclotron resonance. ...